2009
DOI: 10.1002/asia.200900146
|View full text |Cite
|
Sign up to set email alerts
|

Library‐directed Solution‐ and Solid‐phase Synthesis of 2,4‐Disubstituted Pyridines: One‐pot Approach through 6 π‐Azaelectrocyclization

Abstract: An efficient one-pot synthetic procedure for the synthesis of 2,4-disubstituted pyridines has been successfully established. The method proceeds through a 6pi-azaelectrocyclization-aromatization sequence. Using this method, a wide variety of pyridine structures substituted at the 2-position have been rapidly constructed from vinyl stannanes, vinyl iodide, sulfonamide, and a palladium catalyst. The method was further applied to the solid-phase synthesis wherein the use of a "traceless" sulfonamide linker enable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Herein, we describe the application of the TRAM linker (traceless release of acrylamides), 151 the 2-substituted ethylbenzenesulfonate linker 152 and the sulfamylbutyryl linker. 153 Ciolli et al developed a safety-catch TRAM linker for the preparation of small molecules containing an acrylamide moiety (Michael acceptor) via a Hofmann elimination. 151 The synthetic strategy was based on the introduction of acrylamide electrophiles to each library member, which should facilitate the synthesis and identification of small molecules that covalently modify protein targets via proximity-accelerated alkylation.…”
Section: Other Linkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we describe the application of the TRAM linker (traceless release of acrylamides), 151 the 2-substituted ethylbenzenesulfonate linker 152 and the sulfamylbutyryl linker. 153 Ciolli et al developed a safety-catch TRAM linker for the preparation of small molecules containing an acrylamide moiety (Michael acceptor) via a Hofmann elimination. 151 The synthetic strategy was based on the introduction of acrylamide electrophiles to each library member, which should facilitate the synthesis and identification of small molecules that covalently modify protein targets via proximity-accelerated alkylation.…”
Section: Other Linkersmentioning
confidence: 99%
“…The last example in this section is from Katsumura and coworkers. 153 They performed a one-pot synthesis of 2,4disubstituted pyridines through a 6π-azaelectrocyclization− aromatization sequence. Following their previous work, which was performed in solution phase, 155 this strategy was applied to SP synthesis.…”
Section: Other Linkersmentioning
confidence: 99%
“…Several well‐designed pluripotent molecular platforms have been developed by different research groups . Katsumura and Vanderwal's groups have extensively studied substituted dienals possessing well‐defined and dense array of interrelated functionalities . Katsumura and co‐workers found that the introduction of an ester group at the C 3 ‐position of dienals dramatically altered the course of the reaction due to the remarkable accelerating effect of this substituent.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, dienals underwent pericyclic rearrangement in refluxing toluene solution via [1,5]‐H shift of the aldehyde hydrogen to afford the intermediary vinyl ketene intermediate which was subsequently captured by an alcohol, olefin, or imine to afford esters, cyclobutanones, or azacyclobutanones (Scheme ) . They also succeeded in accelerating the key 6π‐aza‐electrocyclization step for the synthesis of multisubstituted piperidine and pyridine derivatives from 1‐azatrienes . The substituent effect was rationalized based on molecular orbital calculation which supports the contention that the substituent at the C 3 ‐position of dienal reduces the activation energy of the process …”
Section: Introductionmentioning
confidence: 99%
“…Although the use of azatrienes with suitable electronic and steric characteristics in 6π-electrocyclization reactions has enabled the synthesis of azaheterocycle natural products, the thermodynamic preferences between dihydropyridines and azatrienes are generally controlled by the azatriene substrates under thermal conditions (Scheme a). Thus, the 1-azatrienes with a leaving group at the nitrogen atom allow facile aromatization to pyridine derivatives, and 1-azatrienes with 4,6-disubstitution are known to facilitate the formation of 1,2-dihydropyridines through conformational and electronic controls . Given the wide synthetic utility of 6π-electrocyclization of 1-azatrienes, it is rather puzzling to find that there are no examples of 6π-electrocyclization of isolated 1-azatrienes derived from N -aryl derivatives .…”
mentioning
confidence: 99%